2020
DOI: 10.3390/app10113823
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Automation for Gravity Compensation of Robotic Arm

Abstract: During the Industry 4.0 era, the open source-based robotic arms control applications have been developed, in which the control algorithms apply for movement precision in the trajectory tracking paths based on direct or reverse kinematics. Therefore, small errors in the joint positions can summarize in large position errors of the end-effector in the industrial activities. Besides the change of the end-effector position for a given variation of the set-point in manipulator joint positions depends on the manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Additionally, this dynamic model can be used to analyze deviations in the tasks of stabilizing the position of manipulation systems installed on non-rigidly stabilized platforms, for example, quadrocopters [22][23][24]. At the same time, parametric perturbations of the platform should be considered as deviations in the 6-DOF joint connecting the manipulating robot to the platform.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this dynamic model can be used to analyze deviations in the tasks of stabilizing the position of manipulation systems installed on non-rigidly stabilized platforms, for example, quadrocopters [22][23][24]. At the same time, parametric perturbations of the platform should be considered as deviations in the 6-DOF joint connecting the manipulating robot to the platform.…”
Section: Discussionmentioning
confidence: 99%
“…In [35], it is shown that 76% of overweight pediatric patients abandon treatment after 6 months, alleging a lack of time to attend checkups and a lack of tools to support their treatment from home. This problem is highlighted by the World Health Organization (WHO), which suggests that the development of telemedicine and mHealth, in that sense, should include parents or caregivers of children as agents of change during the treatment of patients [1,30]; only in this way could be overcome the barriers of face-to-face visits, long distances and insufficient resources [18,27].…”
Section: Mhealth For Obesity In Pediatric Patientsmentioning
confidence: 99%
“…(3) Gravity compensation of each link: the gravity moment of each joint based on the principle of virtual displacement is derived [16], the electric drive to compensate the gravity of each link is used. In order to achieve gravity feedforward compensation, a PD control method based on a robot model is designed [17]. To solve the problem of tracking errors caused by the gravity of each joint linkage, an adaptive neural network model is designed [18].Further, a PD gravity compensation algorithm based on maximum gravity moment estimation and trigonometric function is proposed based on the spatial geometric characteristics of manipulator and the principle of torque balance [19].…”
Section: Introductionmentioning
confidence: 99%